A Multi-Disciplinary Approach in Teaching Literature - Subur Wardoyo (TEFLIN Journal: A publication on the teaching and learning of English, 1998)
Abstract: This is a personal and qualitative look at the way English Literature is taught at the school where the writer teaches and the way it could be improved by relying not only on the Literature TeachÃÂers but also on teachers of other disciplines. Basically Literature is not a monolithic discipline which could be read and taught by literary theoriticians only, it is actually a pluralistic discipline which is accesÃÂsible to people of any discipline. In fact, even people with no formal academic qualification can enjoy literary texts as well. It is also the purpose of this article to explore how people with different voices of discipline could offer different readings of a literary text.